2005
DOI: 10.1080/17461390500076915
|View full text |Cite
|
Sign up to set email alerts
|

How does coping change with development? A review of childhood and adolescence sport coping research

Abstract: It is important to study how children and adolescents cope with stressors in sport because effective coping enhances sport experiences and prevents psychological and physiological problems that can lead to sport withdrawal. The purpose of this review was to summarize the existing child and adolescent coping research to establish how coping changes with development in the achievement context of sport. We reviewed and summarized relevant coping research published from 1980 to 2004 using a 'content analysis' appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 57 publications
(99 reference statements)
4
32
0
2
Order By: Relevance
“…3 Pediatric sport is, however, also laden with an array of potential sources of stress, including overemphasis on winning, poor coach/parent-athlete relationships, antisocial involvement, and pressure for young people to succeed. 4,5 Constructive behavior by parents and coaches is critical for enjoyable and developmentally appropriate sport experiences and sport outcomes for pediatric athletes. However, organized soccer provides ample opportunity for both constructive and detrimental coach and parental involvement.…”
mentioning
confidence: 99%
“…3 Pediatric sport is, however, also laden with an array of potential sources of stress, including overemphasis on winning, poor coach/parent-athlete relationships, antisocial involvement, and pressure for young people to succeed. 4,5 Constructive behavior by parents and coaches is critical for enjoyable and developmentally appropriate sport experiences and sport outcomes for pediatric athletes. However, organized soccer provides ample opportunity for both constructive and detrimental coach and parental involvement.…”
mentioning
confidence: 99%
“…For instance, Parent, Kristiansen, and MacIntosh (2014) found that several Norwegian athletes mentioned security as a stressor, feeling that it was a draining experience that caused some anxiety for them during the YOGs in Innsbruck. While it can be argued that this is a part of elite-level competition and that therefore the line extension acts as practice for athletes to participate in the 'big-event' , it can also be said that the coping strategies needed and the maturity level to deal with the competition stress themselves are areas underdeveloped in younger people (Holt, Hoar, and Fraser 2005). Hanton, Fletcher, and Coughlan (2005) indicated that athletes will experience a mixture of different stressors at sport events including organizationally led stressors, the competition environment and personal sources, all of which can be detrimental to performance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Although participation in sports activities has beneficial effects on both the physical and mental health of children and adolescents, it can be a source of stress and anxi-ety, due to an overemphasis on winning; the pressure to succeed; and poor relationships with coaches, parents, or peers (Holt et al 2006;Ommundsen et al 2006). Further, interpersonal violence, such as sexual harassment, physical abuse, and verbal abuse, is also one of the negative aspects of sports activities, which have a seriously negative impact on the physical and psychological health of young athletes and lead to impaired performance, cessation of sports activities, and psychosomatic illnesses (Mountjoy et al 2016).…”
Section: Introductionmentioning
confidence: 99%